2021
DOI: 10.3390/jcm10132911
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Adjacent Segment Pathology and Facet Joint Violation by Pedicle Screw after Posterior Lumbar Instrumentation Surgery

Abstract: Transpedicular screw instrumentation systems have been increasingly utilized during the fusion of lumbar spine procedures. The superior segment facet joint violation of the pedicle screw is thought to have potential for accelerating symptomatic adjacent-segment pathology (ASP). The purpose of this study was to investigate the relationship between the superior segment facet joint violation by transpedicular screws and the development of ASP. Among all patients who underwent operations involving one- or two-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Several studies have shown links between pedicle screw fixation and adjacent segment degeneration (ASD), particularly at the suprajacent level. [30][31][32] These studies also cite facet joint violation as a potential influencing factor, emphasising the importance of facet stabilisation in achieving good clinical outcomes. [30][31][32] The models developed in this FE study simulated traditional pedicle screw trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown links between pedicle screw fixation and adjacent segment degeneration (ASD), particularly at the suprajacent level. [30][31][32] These studies also cite facet joint violation as a potential influencing factor, emphasising the importance of facet stabilisation in achieving good clinical outcomes. [30][31][32] The models developed in this FE study simulated traditional pedicle screw trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…As lumbar fusion has become increasingly used in clinical practice, the incidence of ASD, one of the late complications of this procedure, has also increased gradually [ 7 ]. Superior FJV, as an important risk factor for ASD [ 6 8 ], has attracted increasing attention. Since screw malposition may cause serious complications [ 32 ], the safety and accuracy of screw placement are critical.…”
Section: Discussionmentioning
confidence: 99%
“…ASD has become the major cause of revision surgical procedures after lumbar fusion [ 3 ]. Recent studies have shown that cranial facet joint violation (FJV) is an important risk factor for ASD [ 4 8 ]. Injury to the superior facet joints during the placement of pedicle screws was associated with alterations in stability and the load-bearing capability of the adjacent segment [ 9 – 11 ], thus accelerating the degeneration of the joint and ultimately leading to ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with percutaneous BPS technique, the significant reduction in soft tissue damage is an advantage of percutaneous TFS technique, leading to less functional loss of muscle along with decreased infection rate [ 24 ]. In addition, the most cephalad screw or rod in the construct of percutaneous pedicle screw fixation may mechanically compromise the adjacent facet [ 31 ], which will lead to an increase in the degeneration of adjacent segments [ 32 ]. Differently, no injury of adjacent facets is triggered by transfacet screw fixation due to its entry point and direction and unnecessary rod usage [ 33 ].…”
Section: Discussionmentioning
confidence: 99%